Characterization of cord blood CD3+TCRVα7.2+CD161high T and innate lymphoid cells in the pregnancies with gestational diabetes, morbidly adherent placenta, and pregnancy hypertension diseases. (1st May 2022) - Haliloglu, Yesim; Ozcan, Alper; Erdem, Serife; Azizoglu, Zehra Busra; Bicer, Ayten; Ozarslan, Ozcan Yeniay; Kilic, Omer; Okus, Fatma Zehra; Demir, Fatma; Canatan, Halit; Karakukcu, Musa; Uludag, Semih Zeki; et al.
Abstract: Problem: Although pregnant women with gestational diabetes (GD), morbidly adherent placenta (MAP), and pregnancy hypertension (pHT) diseases lead to intrauterine growth restriction (IUGR), little is known about their effect on mucosal‐associated invariant T (MAIT) and innate lymphoid cells (ILC) in the umbilical cord. This study aimed to quantify and characterize MAIT cells and ILCs in the cord blood of pregnant women with GD, MAP, and pHT diseases. Method of study: Cord blood mononuclear cells (CBMCs) were isolated by Ficoll‐Paque gradient. CD3 + TCRVα7.2 + CD161 high cells and ILC subsets were quantified by flow cytometry. CBMCs were stimulated with PMA/Ionomycin and Golgi Plug for 4 h and stained for IFN‐γ, TNF‐α, and granzyme B. The stained cells were analyzed on FACS ARIA III. Results: Compared with healthy pregnancies, in the cord blood of the pHT group, elevated number of lymphocytes was observed. Moreover, the absolute number of IFN‐γ producing CD4 + or CD4 − subsets of CD3 + TCRVα7.2 + CD161 high cells as well as those producing granzyme B were significantly elevated in the pHT group compared to healthy controls suggesting increased MAIT cell activity in the pHT cord blood. Similarly, in the MAP group, the absolute number of total CD3 + TCRVα7.2 + CD161 high cells, but not individual CD4 + or negative subsets, were significantly increased compared with healthy controls' cord blood. Absolute numbers of total CD3 + TCRVα7.2 + CD161 high cells and their subsets were comparable in the cord blood of the GD group compared with healthy controls. Finally, the absolute number of total ILCs and ILC3 subset were significantly elevated in only pHT cord blood compared with healthy controls. Our data also reveal that IFN‐γ + or granzyme B + cell numbers negatively correlated with fetal birth weight. Conclusions: CD3 + TCRVα7.2 + CD161 high cells and ILCs show unique expansion and activity in the cord blood of pregnant women with distinct diseases causing IUGR and may play roles in fetal growth restriction.